The Weibull Marshall–Olkin Lindley distribution: properties and estimation. Issue 1 (1st January 2020) - Afify, Ahmed Z.; Nassar, Mazen; Cordeiro, Gauss M.; Kumar, Devendra
Abstract : We obtain some properties of the Weibull Marshall–Olkin Lindley distribution. Its hazard rate function can be increasing, decreasing, bathtub-shaped, decreasing-increasing-decreasing and unimodal. We compare the performance of some methods to estimate its model parameters by means of extensive simulations. The potentiality of the new distribution to modeling real-life data is shown using two real data sets.